Development and application of a preliminary design methodology for modern low emissions aero combustors - Liu, Yize; Sun, Xiaoxiao; Sethi, Vishal; Li, Yiguang; Nalianda, Devaiah; Abbott, David; Gauthier, Pierre Q.; Xiao, Bairong; Wang, Lu (Sage, 2020)
In this article, a preliminary design framework containing a detailed design methodology is developed for modern low emissions aero combustors. The inter-related design elements involving flow distribution, combustor sizing, heat transfer and cooling, emission and performance are coupled in the design process. The physics-based and numerical methods are provided in detail, in addition to empirical or semi-empirical methods. Feasibility assessment on the developed work is presented via case studies. The proposed combustor sizing methodology produces feasible combustor dimensions against the public-domain low emissions combustors. The results produced by the physics-based method show a reasonable agreement with experimental data to represent NOx emissions at key engine power conditions. The developed emission prediction method shows the potential to assess current and future technologies. A two-dimensional global prediction on liner wall temperature distribution for different cooling systems is reasonably captured by the developed finite difference method. It can be of use in the rapid identification of design solutions and initiating the optimisation of the design variables. The altitude relight efficiency predicted shows that the method could be used to provide an indicative assessment of combustor altitude relight capability at the preliminary design phase. The methodology is applied and shows that it enables the automatic design process for the development of a conceptual lean staged low emissions combustor. The design evaluation is then performed. A sensitivity analysis is carried out to assess the design uncertainties. The optimisation of the air distribution and cooling geometrical parameters addresses the trade-off between the NOx emissions and liner wall cooling, which demonstrates that the developed work has potential to identify and solve the design challenges at the early stages of the design process.
Keywords: Preliminary design; low emissions combustors; aero-engine; performance; optimisation